Too Much of a Good Thing: How Ectopic DNA Replication Affects Bacterial Replication Dynamics - Syeda, Aisha H.; Dimude, Juachi U.; Skovgaard, Ole; Rudolph, Christian J. (Frontiers in Microbiology, 2020)
Each cell division requires the complete and accurate duplication of the entire genome. In bacteria, the duplication process of the often circular chromosomes is initiated at a single origin per chromosome, resulting in two replication forks that traverse the chromosome in opposite directions. DNA synthesis is completed once the two forks fuse in a region diametrically opposite the origin. In some bacteria, such as Escherichia coli, the region where forks fuse forms a specialised termination area. Polar replication fork pause sites flanking this area can pause the progression of replication forks, thereby allowing forks to enter but not to leave. Transcription of all required genes has to take place simultaneously with genome duplication. As both of these genome trafficking processes share the same template, conflicts are unavoidable. In this review we focus on recent attempts to add additional origins into various ectopic chromosomal locations of the E. coli chromosome. As ectopic origins disturb the native replichore arrangements, the problems resulting from such perturbations can give important insights into how genome trafficking processes are coordinated and the problems that arise if this coordination is disturbed. The data from these studies highlight that head-on replication-transcription conflicts are indeed highly problematic and multiple repair pathways are required to restart replication forks arrested at obstacles. In addition, the existing data also demonstrate that the replication fork trap in E. coli imposes significant constraints to genome duplication if ectopic origins are active. We describe the current models of how replication fork fusion events can cause serious problems for genome dupli¬cation, as well as models how such problems might be alleviated both by a number of repair pathways as well as the replication fork trap system. Considering the problems associated both with head-on replication-transcription conflicts as well as head-on replication fork fusion events might provide clues of how these genome trafficking issues have contributed to shape the distinct architecture of bacterial chromosomes.